BAHAN AJAR WORKSHEET MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN - Adawiyah, Rabihatun; Hardianti, Farlina; Fitriani, Rohyana (Universitas Hamzanwadi, 2023)
Study aims to develop worksheet teaching materials products and to determine the effect of worksheet teaching materials on the early reading ability of children aged 5-6 years at KB Nurul Iman Ketangga the academic year 2022/2023. The type of research used in this study is experimental method. The research design used was pre-experimental in the form of One-Group pretest- posttest design. The subjects of this study were all 15 children of group B1 KB Nurul Iman. The instruments used to collect data are in the form of validation sheets, observation sheets and documentation. In addition, it can also be seen from the results of hypothesis testing with a value of ??????>?????? (12.94 > 2.145). So it can be concluded that the worksheet teaching materials are effectively used to improve the early reading skills of children aged 5-6 years at KB Nurul Iman Ketangga.